Effect of Pursed Lips Breathing (PLB) on Increased Oxygen Saturation in Chronic Obstructive Pulmonary Disease (COPD) Patients: Literature Review - Yari, Yarwin; Rohmah, Ulfa Nur; Prawitasari, Shinta (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2023)
Introduction: Pursed-lips breathing (PLB) is a breathing exercise performed on patients with chronic obstructive pulmonary disease (COPD) to relieve symptoms of dyspnea so that the patient's oxygen saturation value increases, and its practice is widely taught as a breathing strategy to increase tolerance in performing activities. Objective: Determine the effect of pursed lips breathing (PLB) on increasing oxygen saturation in patients with chronic obstructive pulmonary disease (COPD). Method: This study used the method of literature review study. Result: Initial search results found as many as 4011 potential articles. After discarding articles identified as duplication and relevance to the topic, there were 6 articles that met the theme of the literature study, the six journals discussed the effectiveness of PLB in COPD patients. Conclusion: PLB is able to increase the patient's oxygen saturation value, so PLB intervention is recommended for COPD patients with dyspnea symptoms.